Profitabilitas sebagai Pemoderasi Pengaruh Pertumbuhan Perusahaan pada Nilai Perusahaan - Dharmayusa, Dewa Putu; Suaryana, I Gusti Ngurah Agung (E-Jurnal Akuntansi; Vol 31 No 10 (2021), 2021)
This study aims to prove empirically the effect of companies growth to companies value with profitability as moderating. This study done at manufacturing companies in consumer goods sector that listed on the IDX. Sample were selected using with non-probability sampling method with purposive sampling technique. Total observation on this study is 60 observations for period 2015-2017. Analysis technique that used is Moderated Regression Analysis (MRA). The result of this study show companies growth and profitability doesn’t affect companies value. Profitability didn’t capable to moderating companies growth in affecting companies value.  Keywords: Companies Value;  Companies Growth; Profitability.